2012
DOI: 10.1634/theoncologist.2010-0181
|View full text |Cite
|
Sign up to set email alerts
|

Neoplasms Associated with Germline and Somatic NF1 Gene Mutations

Abstract: After completing this course, the reader will be able to:1. Describe phenotypic and clinical features associated with neurofibromatosis 1. Identify malignant tumors associated with neurofibromatosis 1.This article is available for continuing medical education credit at CME.TheOncologist.com. CME CME ABSTRACTIntroduction. Neurofibromatosis 1 is a tumor predisposition genetic syndrome with autosomal dominant inheritance and virtually 100% penetrance by the age of 5 years. NF1 results from a loss-of-function muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 224 publications
(258 reference statements)
3
62
0
8
Order By: Relevance
“…Embryonal rhabdomyosarcoma (eRMS) Although the prevalence of embryonal rhabdomyosarcoma in NF1 populations had been estimated as high as 1.4% to 6%, larger series confirm a risk of less than 1% (17,45,46) but still higher than in the general population. The urogenital system is the most common anatomic site involved, although other localizations have been reported (orbit is the second most frequent localization).…”
Section: Malignancies In Nf1mentioning
confidence: 99%
“…Embryonal rhabdomyosarcoma (eRMS) Although the prevalence of embryonal rhabdomyosarcoma in NF1 populations had been estimated as high as 1.4% to 6%, larger series confirm a risk of less than 1% (17,45,46) but still higher than in the general population. The urogenital system is the most common anatomic site involved, although other localizations have been reported (orbit is the second most frequent localization).…”
Section: Malignancies In Nf1mentioning
confidence: 99%
“…Patil and Chamberlain reviewed the literature for neoplasm associated with germline and somatic NF1 gene mutations (6). Treatment is the same with sporadic breast cancer cases.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The NF1 gene contains a GAP domain with a conserved arginine finger motif. 16 Taken together, the facts that clinical NF1 is a dominantly inherited cancer predisposition syndrome, NRAS and KRAS are frequently mutated in human cancers, and neurofibromin is a Ras GAP 16,17 suggested that NF1 was a bona fide tumor suppressor gene.…”
Section: Nf1mentioning
confidence: 99%